2021
DOI: 10.3390/v13081471
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Pseudotyping of Different Retroviral Vectors Using a Novel, Codon-Optimized Gene for Chimeric GALV Envelope

Abstract: The Gibbon Ape Leukemia Virus envelope protein (GALV-Env) mediates efficient transduction of human cells, particularly primary B and T lymphocytes, and is therefore of great interest in gene therapy. Using internal domains from murine leukemia viruses (MLV), chimeric GALV-Env proteins such as GALV-C4070A were derived, which allow pseudotyping of lentiviral vectors. In order to improve expression efficiency and vector titers, we developed a codon-optimized (co) variant of GALV-C4070A (coGALV-Env). We found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…There is also a technical concern that the addition of SeV-HN plasmid DNA increases the total amount of DNA for LV production. Codon optimization of the viral envelope protein significantly reduces plasmid consumption [ 44 ]. Therefore, we attempted to minimize the SeV-HN plasmid vector and constructed HN with the Kozak sequence (kHN) and human codon-optimized HN with the Kozak sequence (khcHN) to increase the levels of SeV-HN envelope protein in the LV particles ( Figure 3 A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also a technical concern that the addition of SeV-HN plasmid DNA increases the total amount of DNA for LV production. Codon optimization of the viral envelope protein significantly reduces plasmid consumption [ 44 ]. Therefore, we attempted to minimize the SeV-HN plasmid vector and constructed HN with the Kozak sequence (kHN) and human codon-optimized HN with the Kozak sequence (khcHN) to increase the levels of SeV-HN envelope protein in the LV particles ( Figure 3 A).…”
Section: Resultsmentioning
confidence: 99%
“…The careful balance of the two envelope proteins in viral particles to provide maximum effectiveness is crucial for dual-pseudotyped viral vectors. Moreover, despite the codon-optimization approach allowing for the synthesis of a large amount of protein using only a small amount of plasmid during the transient transfection, it has been less frequently used for viral envelope proteins [ 44 ]. We achieved technical optimization and showed that 0.1 unit of pCAG-khcHN (human codon-optimized SeV-HN with the Kozak sequence) plasmid vector per 1.0 unit of pCMV-VSV-G plasmid vector is adequate to maintain the balance of VSV-G and SeV-HN in the viral particles for V/HN-LV production.…”
Section: Discussionmentioning
confidence: 99%
“…Retroviral vector particles pseudotyped with the Gibbon-ape leukemia virus (GALV) envelope were produced by transiently transfecting HEK293T cells. To do so, we used the calcium phosphate method and titrated the obtained vector containing supernatants on HEK293T, both steps as described previously [21]. Titers of concentrated (by centrifugation) supernatants were in the range of 1-60 ×10 6 transducing units per mL.…”
Section: Retroviral Transductionmentioning
confidence: 99%
“…Cancers 2024, 16, x FOR PEER REVIEW 4 of 18 calcium phosphate method and titrated the obtained vector containing supernatants on HEK293T, both steps as described previously [21]. Titers of concentrated (by centrifugation) supernatants were in the range of 1-60 ×10 6 transducing units per mL.…”
Section: Crispr/cas Rnp Generation and Transfectionmentioning
confidence: 99%